AnimeGhoul8863:

Given the equation 2(3x − 4) = 5x + 6, solve for the variable. Explain each step and justify your process. Charlie solved a similar equation below. Is Charlie's solution correct? Explain why or why not. 4x − 3 = 2(x − 1) 4x − 3 = 2x + 2 2x − 3 = 2 2x = 6 x =3

3 months ago
TheSmartOne:

Let's do the first question. Can you distribute 2 in 2(3x-4)

3 months ago
TheSmartOne:

What even is this sorcery

3 months ago
TheSmartOne:

Let's take it step by step So we need to distribute. I'll show you an example so you can understand 5(3x-6) = (5*3x) - (5*6) = 15x - 30 Now can you do the same for 2(3x-4) @animeghoul8863

3 months ago
AnimeGhoul8863:

2(3x − 4) = 5x + 6 Step 1: (2*3x) - (2*4)

3 months ago
AnimeGhoul8863:

^like that

3 months ago
AnimeGhoul8863:

2(3x − 4) = 5x + 6 Step 1: (2*3x) - (2*4) =6-8

3 months ago
TheSmartOne:

Don't bother with writing steps, just do as I say and I'll show you how to write it all together

3 months ago
TheSmartOne:

So you made a mistake 2*3x = 6x You can't forget that x, it's a variable and needs to stay

3 months ago
AnimeGhoul8863:

2(3x − 4) = 5x + 6 (2*3x) - (2*4) =6x-8 6x-8=5x+6

3 months ago
TheSmartOne:

Good good, we're on the right track now

3 months ago
AnimeGhoul8863:

2(3x − 4) = 5x + 6 (2*3x) - (2*4) =6x-8 6x-8=5x+6 +8 +8 simplify 6x=5x+14 -5 -5 x=14

3 months ago
AnimeGhoul8863:

^^^^^ hows that *pant pant pant*

3 months ago
TheSmartOne:

Uh-oh, slight mistake You were subtracting 5x not 5 But then next step is correct that x=14 Think of it like this that the 'x' is an apple I have 5x or 5 apples If you give me some apples so that I now have twice as.many apples I have 2*5x or 10apples And then you decide to give me their number 2. It's just a number That means I have 10x + 2 Not 12x, not 12 I don't have 12 apples or my apples don't disappear into a random number Does that make sense But you're getting a good grasp on things so far, so good job!!

3 months ago
TheSmartOne:

Your profile picture is so confusing because it looks like you're typing

3 months ago
AnimeGhoul8863:

2(3x − 4) = 5x + 6 (2*3x) - (2*4) =6x-8 6x-8=5x+6 +8 +8 simplify 6x=5x+14 -5x -5x x=14

3 months ago
AnimeGhoul8863:

so as long as it looks like this its correct

3 months ago
TheSmartOne:

I guess it's fine, that format would look much better if it's written on paper tbh

3 months ago
AnimeGhoul8863:

im sorry but im homeschooled and have to hand it in online i cant put it on paper but would it be correct if i kept it this way

3 months ago
TheSmartOne:

Yeah I know, that way should be fine. Your teacher should understand it

3 months ago
AnimeGhoul8863:

ok part B

3 months ago
TheSmartOne:

Yes, what mistakes did you catch

3 months ago
AnimeGhoul8863:

2x − 3 = 2

3 months ago
TheSmartOne:

Also look at 2(x-1) what should 2(x-1) be

3 months ago
AnimeGhoul8863:

4x − 3 = 2(x − 1) <<<<<< 2x-1? 4x − 3 = 2x + 2 2x − 3 = 2<<<<<<< because 4x-3=2x+2 simplified = 5 2x = 6 x =3

3 months ago
TheSmartOne:

Also we should always try to find the first mistake done because that's were it got derailed first

3 months ago
TheSmartOne:

It should be 2x-2 You have to multiple the 2 across and a minus

3 months ago
AnimeGhoul8863:

4x − 3 = 2x-2 4x − 3 = 2x + 2 2x − 3 = 2<<<<<<< because 4x-3=2x+2 simplified = 5 2x = 6 x =3

3 months ago
AnimeGhoul8863:

so like that

3 months ago
TheSmartOne:

Err We need to work on distributing Solve these random questions. You really need to understand this because this is a basic concept 2 different questions 2(4x + 7) = 2(4x - 7) =

3 months ago
AnimeGhoul8863:

(2*4x)+(2*7)=8x+14=22 (2*4x) - (2*7)= 8-14=6

3 months ago
AnimeGhoul8863:

@TheSmartOne

3 months ago
TheSmartOne:

Ahh That's where you're messing up You can't add apples and oranges 8x+ 14 stays as 8x + 14 8x has an x, 14 does not You cannot add them Does that make sense

3 months ago
AnimeGhoul8863:

yes

3 months ago
TheSmartOne:

Good, now distributing isn't that easy so let me give you another question so you can handle the other type -5(x-4) = -5(x+4) =

3 months ago
AnimeGhoul8863:

ummmmmmm i dont know i havent done this i dont think

3 months ago
TheSmartOne:

It's ok, it's practically the same except now we have a negative Which means we have to distribute them negative sign as well which means sign flips inside

3 months ago
AnimeGhoul8863:

4x − 3 = 2x-2 4x − 3 = 2x - 2 +3 +3 simplify 4x=2x+1 -2x -2x simplify 2x=1

3 months ago
AnimeGhoul8863:

how did i do this time :3

3 months ago
AnimeGhoul8863:

did i do it correctly

3 months ago
AnimeGhoul8863:

@TheSmartOne

3 months ago
AnimeGhoul8863:

4x − 3 = 2x-2 4x − 3 = 2x - 2 +3 +3 simplify 4x=2x+1 -2x -2x simplify 2x=1 x=1/2 or .5

3 months ago
AnimeGhoul8863:

@TheSmartOne

3 months ago
AnimeGhoul8863:

TSOOO NOOO HE WAS TOOOO YOUNG!!!!!!!!!!!!!!!!!!!

3 months ago
AnimeGhoul8863:

@Shadow

3 months ago
AnimeGhoul8863:

i think TSO died

3 months ago
TheSmartOne:

You solved it correctly, now compare it to Charlie's and see what he did wrong

3 months ago